Fracture strength testing of a self-passivating tungsten alloy at the micrometre scale. Issue 32 (1st December 2016) - Lessmann, Moritz T.; Calvo, Aida; Hardie, Christopher D.; Porton, Michael; Ordás, Nerea; García-Rosales, Carmen; Mummery, Paul M.
Abstract: The brittle fracture strength of a self-passivating W-Cr10-Ti2 alloy (in wt.%) was measured through un-notched cantilever bending at the microscopic scale. The material behaved purely elastic and fractured catastrophically in an unstable fashion. An average nominal strength of 5.9 GPa was measured. The scatter in strength was shown to be significantly higher than the sum of all random errors indicating an inherent variability of the material's strength. The measurements from 28 tests followed a Weibull distribution with a modulus of m = 12. Results from a size effect study at the microscopic scale were successfully predicted through Weibull scaling. Extrapolation into the macroscopic range overestimated the measured three-point bend strength, which is likely due to the presence of large-scale heterogeneities. The test technique sampled a material thickness of only several micrometres and is hence suitable for future ion irradiation studies.